Is L. Wittgenstein Analytic or Hermeneutic Philosopher? - Kačerauskas, Tomas (Problemos, 1999)
The purpose of the article is to show a controversy of analytic and hermeneutic, the philosophy of explanation and understanding on basis early (Tractatus Logico-Philosophicus) and late L. Wittgenstein’s (Philosophical Investigations) masterpieces. The linguistic turn of the Tractatus means a reduction of philosophical problems to the problems of logical semantic. It is possible, because early Wittgenstein supposed a unified logical space. The meaning is an equivalent of a proposition and a fact. This “grammar” supposes a unified ontology of the world and his perception. This ontology is close to phenomenological looking. The ideas of early Wittgenstein are most original and influential comparing with Frege’s, Russel’s and Carnap’s views. The author of the Philosophical Investigations modifies the problems of explanation to the problems of understanding. The variety of language games doesn't suppose epistemic monism. So appears philosophy of speech instead of philosophy of language. Then the tasks of philosophy are regrounded. As philosophy or relativism Investigations are close to philosophy of Nietzsche and Heidegger. But the understanding is without ontology. It is an adaptation usage mastering the technique. The picture as a ground of understanding links early and late Wittgenstein. The picture is given with speech, and a harmony of thought and facts in a picture is the • understanding. Late Wittgenstein influenced the late hermeneutic and pragmatic analytic.